Flipchart application for promoting maternal self-efficacy in breastfeeding - Chaves, Anne Fayma Lopes (2015)
Objective: evaluating the effects of using a flipchart as an educational intervention in improving maternal self-efficacy in breastfeeding. Methods: a quasi-experimental study with 41 postpartum women: Intervention Group (n = 20) and Control Group (n = 21) of a public hospital. The intervention consisted of implementing the flipchart “I can breastfeed my baby” in the immediate postpartum and were contacted by telephone after 15 days. For both groups, Breastfeeding Self-Efficacy Scale- Short Form was applied at baseline and after 30 days. Results: before the intervention, the intervention group was 75% with high self-efficacy and 71% of the mothers in the control group of had high self-efficacy. It was found that after educational intervention, all the mothers in the intervention group showed high self-efficacy, while the percentage remained similar to before in the control group (76%). Conclusion: the flipchart had a positive effect on the elevation of self-efficacy in nursingmothers.